The RELATIONSHIP OF VENTILATOR ASSOCIATED PNEUMONIA (VAP) WITH BLOOD GAS ANALYSIS (BGA) : HUBUNGAN KEJADIAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) DENGAN ANALISIS GAS DARAH (AGD) - Darlisman, Napisya Putri; Damanik, Siti Rahmalia Hairani; Nurchayati, Sofiana (Essential English Grammar, 2025)
Ventilator Associated Pneumonia (VAP) is a nosocomial infection that is often experienced by patients who receive mechanical ventilation for more than 48 hours. Various evidence shows that the prognosis for VAP patients is very poor and actions that can be taken to prevent VAP include monitoring the patient's condition through diagnostic examinations, namely blood gas analysis (AGD). This study aims to determine the relationship between the incidence of VAP and AGD. The research design used was correlational with a cross sectional approach. The sample for this research was 67 patient data using purposive sampling technique. The analysis used the Fisher exact test statistical test. The results of this study involved 67 respondents, with the majority of ICU patients aged between 20 and 60 years (43,3%)  and most of them were men (55,2%). The most common occupation among respondents was self-employment (35,8%). VAP positive result (41,8%) and based on the results of blood gas analysis, it showed that (32.8%) patients had respiratory acidosis, (20.9%) had respiratory alkalosis, (10.4%) had metabolic acidosis, (14.9%) had metabolic alkalosis. The results of the bivariate analysis showed that there was a relationship between the ventilator associated pneumonia variable and the blood gas analysis variable with a p value of 0.00 <? (0.05). In conclusion, patients who are on a ventilator are at risk of developing VAP. Patients on ventilators need to have their Clinical Pulmonary Infection Score (CPIS) checked regularly and need to implement strict VAP prevention protocols.